Exploration of Patients' Perceptions About Obstructive Sleep Apnea (OSA) and Their Efforts to Reduce the Risk: A Qualitative Study - Nur Aini; Ollyvia Freeska Dwi Marta; Lilis Setyowati; Erma Wahyu Mashfufa; Tiara Octary (Universitas Aisyah Pringsewu, 2023)
Obstructive sleep apnea (OSA) is a health problem that can cause various negative impacts on health, but society considers OSA to be normal. This research aims to determine how the patient's perception and efforts reduce OSA risk. A qualitative study with a phenomenological approach was conducted. Inclusion criteria was experiencing OSA symptoms such as snoring, sleepiness during the day, and often waking up at night. Seven participants met these criteria were taken by purposive and snowball sampling technique. Data were collected through interviews, Epworth Sleepiness Scale (ESS), and STOP-BANG questionnaire (SBQ). The method and time triangulation were used in this study. Data were analyzed using thematic analysis from the Colaizzi approach. Based on the SBQ, all participants have a high risk of OSA, but they perceived OSA as a normal complaint. Three themes were found in this study: participants perceive OSA as a usual complaint, have a perception that OSA does not endanger health, and do not take action to reduce OSA. It is hoped that the results of this study can increase the awareness of nurses to provide education about sleep problems to the community because sleep problems have not received much attention in Indonesia.